Sedation quality of alfaxalone associated with butorphanol, methadone or pethidine in cats injected into the supraspinatus or the quadriceps muscle. Issue 8 (August 2022) - Giannettoni, Giacomo; Moretti, Giulia; Menchetti, Laura; Pepe, Arianna; Bellocchi, Federica; Bufalari, Antonello; Nannarone, Sara
Objectives: The aim of this study was to compare the quality of sedation with three different anaesthetic protocols (alfaxalone combined with butorphanol, methadone or pethidine) administered intramuscularly in cats, and to evaluate the influence of the injection site (between supraspinatus and quadriceps muscles) on the onset and quality of sedation. Methods: A total of 151 cats were selected for this study. Cats were sedated with alfaxalone (3 mg/kg) combined with either butorphanol (0.3 mg/kg; n = 50), methadone (0.3 mg/kg; n = 53) or pethidine (5 mg/kg; n = 48). The combination was injected intramuscularly into the supraspinatus (n = 79) or quadriceps muscle (n = 72). The data included a scoring system for the quality of sedation and physiological parameters, such as heart rate (HR), respiratory rate, body temperature and occurrence of mydriasis, monitored during the first 30 mins of anaesthesia. Results: The opioid associated with alfaxalone influenced the overall sedation score, the degree of myorelaxation, the occurrence of mydriasis and HR. The overall sedation score was poorer with butorphanol than with methadone ( P  = 0.008), and butorphanol induced a lower degree of myorelaxation than methadone ( P  = 0.013). The injection into the supraspinatus showed better qualitative results for sedation and a faster onset time (in about 3 mins) than that into the quadriceps ( P <0.001). HR decreased from baseline ( P <0.001) and over time ( P <0.001), mainly in cats of the butorphanol–supraspinatus and pethidine–quadriceps groups ( P  = 0.004). The occurrence of mydriasis was lower after butorphanol than after methadone and pethidine ( P  = 0.025), while the incidence of side effects did not differ among groups. Conclusions and relevance: All three protocols provided a good quality of sedation and allowed performing the scheduled procedure. Moreover, the injection into the supraspinatus muscle showed superior results in all the qualitative scores of sedation and quicker onset time than that into the quadriceps muscle.